2020
DOI: 10.1007/s13399-020-01005-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quantity and quality of organic matter in soil after application of poultry litter and poultry litter biochar—5-year field experiment

Abstract: Changes of the addition of poultry litter (PL) and poultry litter biochar (PLB) on quantitative and qualitative humus parameters in loamy sand were estimated during the 5-year study period. The following properties were determined in soil: pH, total carbon (Ctotal), total nitrogen (Ntotal), humic and fulvic acids, extracted carbon, and non-hydrolysing carbon. Additionally, light absorbance in the solutions of humic acids was computed at the wavelength of 280, 465, and 665 nm. It was demonstrated that organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The application of biochars can improve the soil organic matter with long-term effects. 44 The addition of biochars can improve the stability of aggregates in powdery sandy loam and increase carbon storage in large aggregates, while the increase of carbon storage in large aggregates enhances the physical protection of soil organic matter. 45 Lv et al 46 applied biochars to Artemisia selengensis and found that the soil organic carbon content increased by 32% compared with the control, which was consist with a previous report.…”
Section: Effects Of Biochars On Soil Fertility Of Aquatic Vegetablesmentioning
confidence: 99%
“…The application of biochars can improve the soil organic matter with long-term effects. 44 The addition of biochars can improve the stability of aggregates in powdery sandy loam and increase carbon storage in large aggregates, while the increase of carbon storage in large aggregates enhances the physical protection of soil organic matter. 45 Lv et al 46 applied biochars to Artemisia selengensis and found that the soil organic carbon content increased by 32% compared with the control, which was consist with a previous report.…”
Section: Effects Of Biochars On Soil Fertility Of Aquatic Vegetablesmentioning
confidence: 99%
“…The most popular way to manage BL is to apply it in pasture and cropland, as it supplies nutrients for crops and contributes toward sustainable agriculture goals (Diaz et al., 2008; Diaz et al., 2012). The application of BL also plays a critical role in ecological and agricultural systems such as mineral nutrients provision (Ramos et al., 2017), microbial community structure (Mierzwa‐Hersztek et al., 2018; Yagi et al., 2019), and soil quality improvement (Jarosz et al., 2020; Yang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%